Factors Affecting Students’ Readiness in Studying English for Specific Purposes - Fitriani; Jefri, Riny; Amin, Fatimah Hidayahni; Luhriyani, Seny; Hanafie, Nurharsya Khaer (Celebes Journal of Language Studies, 2024)
This study aimed to identify and describe factors affecting the students’ readiness in studying English for Specific Purposes at the Business English Communication Program. This study used a descriptive qualitative method. The informants in this study were four students at the Business English Communication Program who were selected purposively. This study used interview questions to collect the data. Based on the research results, there are three factors affecting the students’ learning readiness, namely physical conditions (including a healthy diet and regular exercise), learning motivation (career development and the importance of feeling comfortable and confident are the biggest motivations for students in participating in ESP learning), and learning materials (searching for additional information and sources, as well as applying learning materials in real-life contexts in each student's field). It can be concluded that physical and mental health, a high motivation to learn, and active seeking for additional resources are required to apply in learning courses of English for Specific Purposes.